2016
DOI: 10.1016/j.jjcc.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between local production of microRNA-328 and atrial substrate remodeling in atrial fibrillation

Abstract: Local production of miR-328 in the left atrium may be involved in the process of atrial remodeling in patients with AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 29 publications
1
29
0
2
Order By: Relevance
“…Compared with CAD and HF there is much less data from clinical trials reported on circulating miRNAs in diagnostic approaches for AF. Some clinical trials, however, identified circulating miRNAs including miR-499 [44], miR-328 [43,45], miR-150 [46], miR-409-3p, and miR-432 [41], miR-126 [126]. None of the reported miRNAs were validated and all trials refer to rather small patients cohorts.…”
Section: Atrial Fibrillation (Af)mentioning
confidence: 99%
“…Compared with CAD and HF there is much less data from clinical trials reported on circulating miRNAs in diagnostic approaches for AF. Some clinical trials, however, identified circulating miRNAs including miR-499 [44], miR-328 [43,45], miR-150 [46], miR-409-3p, and miR-432 [41], miR-126 [126]. None of the reported miRNAs were validated and all trials refer to rather small patients cohorts.…”
Section: Atrial Fibrillation (Af)mentioning
confidence: 99%
“…In addition, plasma miR-1 levels were also higher in the LAA than in the PV in AF patients. Authors did not inform conditions of sample processing, but they stated that total RNA was extracted using TRIzol LS RNA Isolation Kit (Invitrogen) [1]. …”
Section: Plasma Mirna Involved In Afmentioning
confidence: 99%
“…It is the most common type of arrhythmia in clinical practice, and it is a significant health, social, and economic problem, increasing the risk of stroke, heart failure, and morbidity and disability, especially in the elderly [1]. According to the American Heart Association, AF can be classified as first detected episode of AF, paroxysmal when AF is sustained for less than 7 days and terminates spontaneously (PAF), persistent when AF is sustained beyond 7 days (PersAF, can be long-standing when AF persists for more than 1 year), and permanent when cardioversion attempts have failed or have not been tried [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, although studies have already shown that some miRNAs have different expression profiles between biofluids and tissues, Soeki et al. observed similar expression profiles between atrial tissue and plasma of AF patients, strengthening the idea that miRNAs could be disease specific …”
Section: Discussionmentioning
confidence: 99%
“…It is possible that patients with different types of AF will exhibit different miRNA expression pro- observed similar expression profiles between atrial tissue and plasma of AF patients, strengthening the idea that miRNAs could be disease specific. 10 An important factor is the difference in the expression of the same miRNA between different types of human samples. A study performed by our research group observed that the variability of miRNA could be related to the different types of samples (e.g., plasma, serum, platelet, and whole blood) and the methods of analysis used in studies.…”
Section: Discussionmentioning
confidence: 99%